Web-based Information Management System for Asset Data - Fitria Rachmawati; Dahlia Widhyaestoeti; Muhamad Mustopa; Hersanto Fajri; Fety Fatimah (Universitas Ibn Khaldun Bogor, 2024)
In the digital age, information technology is crucial to human existence. The combination of digital and long distance communication methods can make it easier for people to interact through information technology without having to physically present in a location that is frequently inhospitable. PT. Bino Mitra Sejati is the sole subsidiary of the holding company, PT. Perma Plasindo, Tbk, which operates as a trading company and a stationery or ticket printing business. The information held by PT. Bino Mitra Sejati is still not entirely accurate, and there are insufficient stakeholder requests to assist in implementing a more thoroughly integrated system. In this regard, asset management is necessary to increase operational efficiency and risk that occurs.